Improving the Accessibility of Clinical Practice Placements in Midwifery Education: A Scoping Review - Maharani, Fadiah (Jurnal Kesehatan - STIKes Prima Nusantara, 2025)
Background: Practice placements are critical in pre-registration midwifery education, allowing students to develop clinical competence and confidence by applying theoretical knowledge in real-world settings. However, increasing student numbers and limited placement availability present significant challenges globally. Purpose: This scoping review aimed to explore the types of practice placements currently used in midwifery education and to identify potential strategies to expand placement capacity. Methods: A scoping review methodology was adopted, guided by Arksey and O’Malley’s five-stage framework and reported using PRISMA-ScR guidelines. A comprehensive search of eleven databases and grey literature from July 2000 to July 2023 was conducted. Eligible studies included midwifery student placements in clinical or community-based settings. Data were charted and synthesized narratively to extract key themes. Results: Eleven articles from five countries were included. Two main themes emerged: (1) Types of practice placements and (2) Student experiences. Diverse placements—such as rural settings, student-led clinics, and continuity of care models—offered enriched learning experiences and supported competency development. Placements in community-based or private midwifery practices promoted holistic, woman-centred care. However, students also encountered challenges, including unclear role expectations and work-life balance issues in on-call environments. Conclusion: Expanding midwifery practice placement capacity is vital to meet the growing demand for skilled midwives. Educational institutions and policymakers should consider alternative placement models—including rural and student-led settings, continuity of care models, and midwifery group practices—to ensure sustainable, high-quality learning opportunities. Keywords: Midwifery education; Placement Opportunities; Educational strategies; Scoping review